2022
DOI: 10.3389/feduc.2022.856610
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Education in the Context of COVID-19 Lockdowns and School Closures: Challenges and Resilience Among Adolescent Girls and Young Women in South Africa

Abstract: Gender related vulnerabilities and inequalities place female learners at high risk of school disengagement due to COVID-19 disruptions. Understanding the impacts of school closures and educational disruptions on female learners in South Africa is critical to inform appropriate, gender-sensitive policies, and programs, to mitigate further exacerbation of educational inequalities. We examined the effects that COVID-19 and lockdowns have had on the educational experiences of adolescent girls and young women (AGYW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
(48 reference statements)
1
14
0
1
Order By: Relevance
“…The majority of research 1 on the effects of Covid‐19 in education in Africa has been conducted in South Africa (e.g. Duby et al, 2022 ; Landa et al, 2021 ), with a strong emphasis on learning technologies (e.g. Mhlanga & Moloi, 2020 ) or teachers' experiences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research 1 on the effects of Covid‐19 in education in Africa has been conducted in South Africa (e.g. Duby et al, 2022 ; Landa et al, 2021 ), with a strong emphasis on learning technologies (e.g. Mhlanga & Moloi, 2020 ) or teachers' experiences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the impact of the COVID-19 pandemic on adolescent SRH has focused on the wide-ranging effects of the lockdown [ 43 ]. A recent cross-sectional study in Uganda reported that the lockdown in Uganda, one of the most stringent in SSA disrupted education and increased the risk of teenage pregnancies [ 44 ]. Restricting access to schools during the lockdown impeded the main source of sexual Information available to adolescents in SSA [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the closure of educational institutions greatly affected implementation. During the height of first and second epidemic waves, school closures were instituted, in the periods March-June, and again in July-August 2020 (27). During these periods there were no intervention activities offered at schools, dialogues, in-person peer education groups and other group activities.…”
Section: Effects Of Educational Institution Closures On Implementationmentioning
confidence: 99%